2023
DOI: 10.3390/su15118706
|View full text |Cite
|
Sign up to set email alerts
|

Calculating and Analyzing Carbon Emission Factors of Prefabricated Components

Abstract: The construction industry’s carbon emissions have a considerable impact on the environment, and all countries have pledged to reduce them to achieve low-carbon transformation. The use of prefabricated components is widely recognized as a crucial measure for mitigating carbon emissions. However, there is a scarcity of existing data on the carbon emission factors of prefabricated components (CEFoPC), and few studies have focused on calculating and reducing their carbon emissions. This study presents a novel appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Most researchers have constructed analytical frameworks to guide the development of traffic operation strategies to balance social welfare with private sector profitability [1,[11][12][13][14]. Recent investigations have extended those discussions by providing analytical frameworks to guide the development of traffic operation strategies that consider the complex interplay between social welfare and private profitability [3,[15][16][17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most researchers have constructed analytical frameworks to guide the development of traffic operation strategies to balance social welfare with private sector profitability [1,[11][12][13][14]. Recent investigations have extended those discussions by providing analytical frameworks to guide the development of traffic operation strategies that consider the complex interplay between social welfare and private profitability [3,[15][16][17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, there are a vast number of application examples that can be referenced. As a result, the estimation of carbon emission factors is widely used in calculating the carbon emissions of buildings [87]. However, the method also suffers from the disadvantage of being less able to deal with changes in the emission system itself.…”
Section: The Emission Factor Estimationmentioning
confidence: 99%
“…This paper intends to recycle industrial plastic waste and recycled lightweight bricks to prepare sustainable lightweight concrete, which necessitates an ecological impact assessment. To evaluate this impact, or rather the ecological behavior of the proposed lightweight concrete, the carbon emissions and embodied energy are often evaluated according to references [33,[49][50][51][52][53][54][55][56][57][58][59][60]. Table 4 presents the values of each unit of equivalent carbon emissions and embodied energy for the ingredients used in the current study, as reported in previous studies [51][52][53][54][55][56][57][58][59][60].…”
Section: Ecologicalmentioning
confidence: 99%
“…To evaluate this impact, or rather the ecological behavior of the proposed lightweight concrete, the carbon emissions and embodied energy are often evaluated according to references [33,[49][50][51][52][53][54][55][56][57][58][59][60]. Table 4 presents the values of each unit of equivalent carbon emissions and embodied energy for the ingredients used in the current study, as reported in previous studies [51][52][53][54][55][56][57][58][59][60]. Then, to measure the energy and emissions from all origin constituents, the equation shown below is used as mentioned in reference [55]:…”
Section: Ecologicalmentioning
confidence: 99%
See 1 more Smart Citation